Perbandingan model pembelajaran problem based learning dengan metode mnemonic dan model pembelajaran problem based learning dengan alat peraga terhadap kemampuan penalaran matematis siswa - Ukhrowi, Niqmah Putri (Universitas Sebelas Maret, 2023)
Students' mathematical reasoning abilities are still relatively low, this is due to the passive factor of students (only receiving information from the teacher) and the selection of learning models that are not appropriate to the mathematics learning material. This study compared two experimental classes, namely the first experimental class used the problem based learning model with the mnemonic method and the second experimental class used the problem based learning model with teaching aids. The method used in this research is quasi-experimental, the sampling technique is purposive sampling. The population in this study were class VII students of SMPN 2 Balaraja, totaling 306 students with a total sample of 68 students. The instrument used is an essay test. Hypothesis analysis was carried out using the pooled variance model t-test, because the samples were normally distributed and homogeneous. The results of the pooled variance t-test for the pretest data obtained t_(count)=1.42 and t_(table)=1.997 so there was no significant difference, while for the posttest hypothesis test obtained t_(count)=2.70 and t_ (table) = 1.997, it can be concluded that after being given treatment there are differences in students' mathematical reasoning abilities in the matter of linear equations or variables between students who are given the problem-based learning model using the mnemonic method and the problem-based learning model with visual aids. This shows that the problem based learning model with visual aids is higher than the problem based learning model with mnemonics